Analysis of virulence genes and antimicrobial resistance of Vibrio parahaemolyticus isolated from shellfish in 2018 - Liqian LI; Lin YAO; Caiyun LIN; Fengling LI; Meng QU; Lianzhu WANG; Yuxiu ZHAI; Haijin MU; Yanhua JIANG (Zhongguo shipin weisheng zazhi, 2020)
Objective To analyze the virulence genes and antimicrobial resistance of 140 Vibrio parahaemolyticus strains from shellfish collected from farms and markets. Methods Virulence genes and antimicrobial resistance genes were detected by PCR amplification method, and antimicrobial resistance was determined by disk diffusion test. Results None of the 140 strains carried tdh gene, and trh gene was detected in one strain. All strains were resistant to ampicillin, some strains were resistant to cefazolin, cefuroxime sodium, streptomycin, amikacin, sulphamethoxazole/trimethoprim, tetracycline and florfenicol. All strains were sensitive to cefepime, gentamicin, imipenem, meropenem, ofloxacin and doxycycline. Six strains showed multi-antimicrobial resistance to two or more categories of antimicrobials. The resistance genes strA and strB were detected in streptomycin resistant strains, tetA was detected in tetracycline resistant strains, sul2 was detected in sulphamethoxazole/trimethoprim resistant strains, and floR was detected in florfenicol resistant strain. Conclusion Most of Vibrio parahaemolyticus strains didn't carry virulence genes and showed antimicrobial resistance to a certain extent. Some strains had more than one antimicrobial resistance gene, which exhibited multi-antimicrobial resistance. These results indicated that enhancing the monitoring of pathogenicity and antimicrobial resistance of Vibrio parahaemolyticus in aquatic products should be continued.